Symptomatic fibroepithelial polyp of the nipple in a pediatric patient - Elizabeth J. Hughes; Ethan Y. Song; Hina Sheikh; Wellington J. Davis, III (Elsevier, 2022)
Skin tags are benign growths typically found on intertriginous areas of the body. The most common type of skin tag is the acrochordon, skin-colored papules with short, broad stalks. A rarer type of skin tag is the fibroepithelial polyp (FEP), which tend to be larger, with long, narrow stalks. We evaluated a pediatric patient with a nipple lesion that was intermittently painful and discolored. Simple excision and primary closure was performed with excellent results and relief of symptoms. Pathology revealed benign FEP with a few benign lactiferous ducts at the base of the specimen. While the differential for benign nipple lesions is long, with only 8 documented cases of FEP of the breast and none documented in the pediatric population, this poses a diagnostic challenge. Literature shows that FEPs can grow to a large size over time and become increasingly symptomatic. The benefits of simple excision and primary closure of FEP of the nipple include improved cosmesis, improvement in symptoms, and reassurance for patient and family with benign pathology. Given the rarity of this lesion in both location and patient population, it is important for clinicians to differentiate FEP of the nipple from other benign and malignant growths.